2015
DOI: 10.1097/dcc.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Conflict Management Styles Among Iranian Critical Care Nursing Staff

Abstract: Based on the results of this study, nurse managers need to take these factors into account in designing programs to help nurses constructively manage unavoidable conflicts in health care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 19 publications
3
26
1
1
Order By: Relevance
“…Despite the varying scales used to identify conflict styles in nurses, a common finding in the research articles was that nursing professionals used constructive approaches to handle conflicts. Out of 25 studies reviewed, 11 reported integration or collaboration as the most frequently used conflict‐management style among nursing professionals (Ahanchian, Zeydi, & Armat, ; Al Hamdan, ; Al Hamdan, Norrie, & Anthony, ; Al Hamdan, Nussera, & Masa'deh, ; Al Hamdan, Shukri, & Anthony, ; Ebrahim, Dahshan Aly, & Keshk, ; Johansen & Cadmus, ; Kantek & Kavla, ; Mohamed & Yousef, ; Tabak & Orit, ; Ylitörmänen, ). Of these, five studies examined styles of managing conflict among nurse managers (Al Hamdan, ; Al Hamdan et al., , , ; Kantek & Kavla, ), three studies examined ways of dealing with conflict situations among nurses (Johansen & Cadmus, ; Ahanchian et al., ; Ylitormanen, ), and three studies explored conflict‐management styles in both nurses and nurse managers (Ebrahim et al., ; Mohamed & Yousef, ; Tabak & Orit, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the varying scales used to identify conflict styles in nurses, a common finding in the research articles was that nursing professionals used constructive approaches to handle conflicts. Out of 25 studies reviewed, 11 reported integration or collaboration as the most frequently used conflict‐management style among nursing professionals (Ahanchian, Zeydi, & Armat, ; Al Hamdan, ; Al Hamdan, Norrie, & Anthony, ; Al Hamdan, Nussera, & Masa'deh, ; Al Hamdan, Shukri, & Anthony, ; Ebrahim, Dahshan Aly, & Keshk, ; Johansen & Cadmus, ; Kantek & Kavla, ; Mohamed & Yousef, ; Tabak & Orit, ; Ylitörmänen, ). Of these, five studies examined styles of managing conflict among nurse managers (Al Hamdan, ; Al Hamdan et al., , , ; Kantek & Kavla, ), three studies examined ways of dealing with conflict situations among nurses (Johansen & Cadmus, ; Ahanchian et al., ; Ylitormanen, ), and three studies explored conflict‐management styles in both nurses and nurse managers (Ebrahim et al., ; Mohamed & Yousef, ; Tabak & Orit, ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the nurses indicated that they best resolved conflicts through mutual collaboration. In a cross‐sectional study in Iran, critical care staff nurses were asked to evaluate their own conflict‐resolution styles when managing conflict with peers and indicated that the most dominant style of managing conflict was that of collaborating with others (Ahanchian et al., ; ), while in the United States of America, staff nurses reported using integrating and obliging conflict‐management styles (Johansen & Cadmus, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intensive care includes all critical cares depend on the patient’s life under supervision of the more experienced and more highly qualified physicians and nurses using advanced equipment and facilities (1, 2). Multiple organ dysfunction syndrome (MODS) is the last step in severely ill patients, which occurs following infection and septic shock, tissue damage, excessive hemorrhage, ischemia and severe inflammation (3, 4).…”
Section: Introductionmentioning
confidence: 99%